To solve the equation 10 + 7x - 5 = 5x - 3 + 2(x + 4), we need to simplify both sides of the equation and isolate the variable x.
Let's start by expanding the equation:
10 + 7x - 5 = 5x - 3 + 2x + 8
Next, combine like terms:
7x + 5 - 5 = 5x - 3 + 2x + 8
Simplify further:
7x = 7x - 3 + 2x + 8
Combine like terms again:
7x = 9x + 5
At this point, we have all the x terms on one side of the equation. We can now isolate x by getting rid of the 9x term on the right side. We can do this by subtracting 9x from both sides:
7x - 9x = 9x + 5 - 9x
Simplify:
-2x = 5
Next, divide both sides of the equation by -2 to solve for x:
(-2x)/-2 = 5/-2
This gives us:
x = -5/2
Therefore, the solution to the equation 10 + 7x - 5 = 5x - 3 + 2(x + 4) is x = -5/2.
10+7x-5=5x-3+2(x+4
1 answer